Workshop Manajemen Pembelajaran Berbasis Digital bagi Guru SD di Kota Kulon Kabupaten Garut - Chotijah Fanaqi; Jilani Mahar Faiza; Muhammad Ilham Fadhilah; Dina Fauziah (Penerbit Goodwood, 2022)
Purpose: Digital-based learning management workshop is the existence of new knowledge that can be applied by teachers during the learning process with their students, especially making questions or quizzes using Google Classroom and Google Forms. The subjects of this workshop are the teachers of the State Elementary School 1 Kota Kulon, Garut Kota. Method: A digital-based learning workshop with 2 sessions, namely the presentation of material and the practice of using digital media. Results: Online learning workshops that have been organized by the Garut University Service Team provide new understanding and skills to SDN 1 Kulon City teachers in using various digital platforms that can support the learning process during the Covid 19 pandemic. The drawback of this activity is the limited facilities and infrastructure available owned by teachers to support digital-based learning, as there are still few teachers who have laptops or computers to support learning. Contribution: of this activity is to support schools to encourage the ability of educators to carry out digital-based learning, especially during the pandemic of COVID-19.